2009
DOI: 10.5551/jat.e608
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasma Urotensin-II and Carotid Atherosclerosis are Associated with Vascular Dementia

Abstract: Aim: Human urotensin-(U ) is a cyclic neuropeptide with potent vasoconstrictive activity in the vasculature. The expression of U and its receptor (UT) mRNA is detected at high levels in the brain. We evaluated the relationship between plasma U levels and vascular dementia (VaD) caused by stroke or atherosclerotic small vessel disease. Methods: Carotid artery intima-media thickness (IMT), plaques, plasma levels of immunoreactive U (IR-U ), and atherosclerotic biomarkers were determined in 42 patients with VaD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…33 Moreover, elevated plasma level of UII and expression of UII and the UT have been reported in experimental animals of hypertension, 34,35 and a recent study has shown significant correlation between blood pressure and UII levels in patients with carotid atherosclerosis and vascular dementia. 36 Here we demonstrated that UII KO mice tend to exhibit decreased mean arterial and, particularly, systolic blood pressure than wild type. Similarly, the use of UT antagonist SB657510A significantly reduced mean blood pressure and systolic pressure in apoE KO mice fed a HFD.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…33 Moreover, elevated plasma level of UII and expression of UII and the UT have been reported in experimental animals of hypertension, 34,35 and a recent study has shown significant correlation between blood pressure and UII levels in patients with carotid atherosclerosis and vascular dementia. 36 Here we demonstrated that UII KO mice tend to exhibit decreased mean arterial and, particularly, systolic blood pressure than wild type. Similarly, the use of UT antagonist SB657510A significantly reduced mean blood pressure and systolic pressure in apoE KO mice fed a HFD.…”
Section: Discussionmentioning
confidence: 66%
“…UII has been shown to influence lipase activity in the cohoe salmon, 38,39 and UII plasma level is associated with LDL in atherosclerosis. 36 However, since those initial studies, little has been done to assess the effects of UII on serum lipids. Here, we demonstrated for the first time that deletion of the UII gene alone or in the pathological setting of apoE KO in mice fed a HFD resulted in a decrease in serum LDL and triglycerides and an increase in serum pre-β highdensity lipoprotein as evident in the increase of lipoprotein particles containing apoA-I.…”
Section: Discussionmentioning
confidence: 99%
“…20 In a similar context, U-II might have different effects on the various regions of brain, and because of this variability, U-II could play a role in the etiologies of different neuropsychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there was no reported association between Alzheimer's and U-II levels. 20 These findings indicate that U-II could play a role in vascular dementia's etiology via severe vasoconstriction. U-II is also an important molecule for understanding the brain's blood supply, as well as oxidative and immunological mechanisms.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation